The Kentucky Civil Protective Order Study: A Rural and Urban Multiple Perspective Study of Protective Order Violation Consequences, Responses, and Costs, 2006-2008 - Logan, TK ([Verlag nicht ermittelbar], 2015)
This project examined civil protective orders in Kentucky from multiple perspectives in order to examine rural and urban jurisdictional differences in the protective order process, protective order outcomes, and costs of protective orders, as well as potential avoided costs to society due to the protections that protective orders are supposed to provide. Although partner violence can be perpetrated by both men and women, the vast majority of serious partner violence and protective order use is for cases of male violence against female partners. Thus, this project focused on women victims of partner violence. The study was comprised of three substudies. The first substudy examined rural and urban key informant perceptions along with court records and other secondary data to provide an in-depth picture of jurisdictional differences in the protective order process. The second substudy provided a picture of women's self-reported experiences with violence and the protective order system and its outcomes. This substudy not only provided a description of those who obtain protective orders, but also provided a detailed look at the process of obtaining a protective order as well as the sacrifices and barriers that women experience in obtaining protective orders and trying to get them enforced. This substudy also provided detailed information about protective order effectiveness and enforcement outcomes. The third substudy examined the social and personal costs of abuse and violence, the costs of protective orders, and the potential avoided costs due to the protection protective orders provide. These costs were provided for the sample of women interviewed and were also extrapolated from the sample to the population of victims who obtained protective orders issued in 2007 in Kentucky in order to expand the policy implications of the findings from this substudy. The data file for Part 1 (Key Informant - Substudy 1) contains 188 cases and 502 variables. The data file for Part 2 (Interview data - Substudies 2 and 3) contains 213 cases and 14,644 variables.